Bacteria common to rhizosphere communities of Asiatic bittersweet across a post-glacial landscape - Nakatsu, Cindy H.; Pavlovic, Noel B.; Byappanahalli, Muruleedhara N. (Frontiers in Ecology and Evolution, 2022)
Invasive plants such as Asiatic bittersweet (Celastrus orbiculatus Thunb.) are a significant problem for land managers due to their impact on composition, disrupting nutrient dynamics and structure of native ecosystems, and they are difficult to eradicate. As a result of the increasing abundance of Asiatic bittersweet across the eastern U.S., we have been investigating underlying factors potentially contributing to the success of this plant. Recently, ecologists have been investigating the role of plant-soil-microbe interactions contributing to plant invasion. This leads to the question: are there certain microbes (e.g., bacteria, fungi) contributing to the success of some invasive plants? We hypothesize that despite differences in the soil ecology of Asiatic bittersweet establishment in the Indiana Dunes region there are bacterial taxa common in their rhizosphere. The objectives were to determine differences and commonalities in the soil chemistry, plant community and bacterial communities of Asiatic bittersweet plants. To achieve these objectives bittersweet plants were collected at thirteen locations in the region from soils ranging in geologic age from 150 to over 14,500 years. Surrounding soil chemistry, plant cover and the 16S rRNA gene amplicon sequences of rhizosphere soil bacterial communities of these Asiatic bittersweet were compared. Asiatic bittersweet coverage of sampling sites ranged from 2 to 77% averaging 52 ± 2 %. There were statistically significant differences (p < 0.05) in alpha diversity (Shannon, Faith’s PD and Pielou’s evenness) and beta diversity (Bray Curtis, Jaccard, unweighted Unifrac, weighted Unifrac) among the samples when grouped by soil age or habitat. Despite these differences in the bacterial communities from different soil ages and habitats, some bacterial taxa (e.g., Bacillus, Streptomyces, Sphingomonas and Rhizobiales) previously found in other studies to be beneficial to plant growth were found in every rhizosphere community sampled. These microbes provide insight into the success of this invasive plant at the Indiana Dunes National Park, and a strategy for future work to reduce the impact of Asiatic bittersweet establishment and offer some new strategies to manage this nuisance species.